Integrated Management Systems - Chovancova, Jana; Majerník, Milan; Jurikova, Jana (Communications - Scientific letters of the University of Zilina, 2010)
Over the past few years an increasing number of companies certified according to the requirements of ISO 9001:2008 for Quality Management System (QMS) but also according to the requirements of other standards, for example environmental management system according to ISO 14001:2004 (EMS) and / or a management system for Occupational Health & Safety Management System, according to OHSAS 18001:2007, or other standards (ISO 22000, ISO 27000, etc.) can be seen in industrial sector and in services as well. Integration of management systems has become a key aspect of more sustainable management of a company. The aim of paper is to (1) better explain role of management systems implementation in enterprises, (2) point out necessity of their integration, (3) analyze common items of particular management systems, which is inevitable to their further integration, (4) point out some benefits and obstacles linked with integration.